Ventriculosubgaleal shunt versus External Ventricular Drain in the treatment of Acute Hydrocephalus in Adults (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Hydrocephalus is caused by subarachnoid hemorrhage (SAH), intraventricular hemorrhage (IVH), Infection or by a tumor compressing the CSF passages is mostly temporary and can resolve with treatment. We have many methods to assure cerebrospinal fluid (CSF) diversion, no method is considered more preferable than others; so, to choose a method depends on the causes or other factors.Ventriculosubgaleal shunt (VSGS) is one of those temporary ways in which we can assure a simple and rapid CSF decompression method and not causing electrolytes or nutritional losses.To study the effectiveness of using VSGS compared to external Ventricular Drain (EVD) in adult hydrocephalus for temporary CSF conversion and to find out the results that help us avoid putting a permanent shunt, and last, to find the possibility of occurrence of complications.  A retrospective observational study.Materials and Methods: The data were taken from Hospital Admission notes of fifty patients with acute hydrocephalus: 26 caused by IVH, 10 from ruptured aneurysm, 8 post-traumatic, and 6 were due to infection. In all the patients we did CSF conversion in Hospital Queen Elizabeth II, Sabah, Malaysia, from 2012 to 2015. The patients’ follow-up started from the date of surgery till the hydrocephalus is treated completely Parameters used are the dependency to the shunt and the occurrence of complications.  Statistical Packages for the Social Sciences Version 22.0. Chi squared test, Fisher’s exact test.Results: A total of 21 (42%) patients, EVD inserted and 29 (58%) VSGS inserted. Thirty-seven (74%) patients did not need a permanent shunt; 24 (64.8%) of them were from the VSGS group (P = 0.097). EVD patients developed more complications (44.1%) in comparison to VSGS (23.5%), with a statistically significant difference P = 0.026.Conclusions: VSGS is a safe and a dependable way for adult hydrocephalus patient’s treatment, with the ability to continue the treatment for such patients in non-neurosurgical centers or even discharge the patient home, as compared to patients with EVDs. This method does not have a statistical difference to avoid putting a ventriculoperitoneal shunt, VSGS has a significant less complications than EVD.